SHORTENING AND ITS CHARACTERISTIC FEATURES. - Khaydarova Nigora; Madaminova Gulzoda (TADQIQOTLAR, 2025)
Annotation: This article explores the phenomenon of shortening in the English language, which is one of the most productive and dynamic word-formation processes. It analyzes the types, characteristics, and functions of shortened forms, and their signifi cance in modern communication.